FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT BAWEAN DALAM MEMILIH BANK SYARIAH - Salis, Nur; Solekah, Nihayatu Aslamatis (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Indonesia Sharia banks need to be developed because they have comprehensive advantages over conventional banking. To reach services to the community, it is necessary to expand in developing a network of Sharia Bank offices. Therefore there must be an effort from Sharia banking increases public interest in Sharia Banks so that it can be developed. The purpose of this study is to find out what factors influence the interest of the Bawean community in choosing a Sharia Partner Bank and to find out what the most dominant factors influence the interest of Bawean community in choosing Sharia Partner Bank. This study uses descriptive quantitative method. The population of this study is 165 samples of Bawean community and the sampling technique used purposive sampling. The data analysis technique uses Partial Least Squares (PLS) analysis which is a Structural Equation Modelling (SEM). The result of this study indicate that the marketing mix factor, internal individual consumers and external individual consumers influence the interest of the Bawean communityÂ in choosing Sharia Partner Banks. While the marketing mix factor is the most dominant factor affecting the interest of the Bawean community in choosing Sharia Partner Banks.